Implementation of compound optimal design strategy in censored life-testing experiment - Bhattacharya, Ritwik (Test (Madrid, Spain), 2020)
Single-objective optimal designs or constraint optimal designs have widely been studied in life-testing experiment literature. However, the experiments having multiple objectives did not get relevant attention so far. Compound optimal designs are usually employed in statistical design problems where the experiment possesses multiple goals. This article introduces the concept of compound optimal design in life-testing experiments. A graphical solution approach is developed to find the optimal design, which is easy to compute and interpret. At the end, the equivalence of the compound optimal design and the constraint optimal design has been established. The advantage of using compound optimal design over the constraint optimal design is demonstrated through one example. Finally, one real-life data set is analyzed to in life-testing experiment illustrate the applicability of the proposed approach in practice.